0388 An update of mortality and cancer incidence among Ontario uranium miners exposed to radon progeny. (23rd June 2014) - Navaranjan, Garthika; Kone, Anna; Berriault, Colin; Do, Minh; J Villeneuve, Paul; Marrett, Loraine; A Demers, Paul
Abstract : Objectives: Underground uranium mining and milling was conducted in Northern Ontario from 1955 to 1996. The Ontario uranium miner's cohort was created to study the health effects of radon and other occupational exposures. Study objectives include providing updated estimates of cancer incidence and mortality for miners exposed to radon daughters, a project funded by the Canadian Nuclear Safety Commission. Method: The cohort of mine and mill workers was created using data from the National Dose Registry (Canada's ionising radiation exposure registry), and the Ontario Mining Master File (containing work history information collected during annual chest x-rays) data. The cohort consists of men who worked for at least one week between 1954 and 2004. Follow-up was recently extended from 1986 to 2007 for mortality and included follow-up for cancer incidence from 1969–2005. Standardised mortality ratios (SMRs), standardised incidence ratios (SIRs) and their 95% confidence intervals (CIs) will be calculated based on Canadian national reference rates. Results: The final cohort consisted of 28 546 miners. The mean age of the miners at entry into the study was 28.8 years. Miners in the cohort had a mean cumulative exposure of 21.0 WLM over an average of 5.3 years of total exposure. Between 1954 and 2007, a total of 8572 deaths were observed, and of these 2809 were due to cancer, including 1246 lung cancer deaths. There were 4151 incident cancers, including 1285 lung cancers, observed. Conclusions: The Ontario uranium miner's cohort study continues to be a valuable source of assessing uranium miners risk of cancer mortality and incidence.